Comparative analysis of root transcriptome profiles between drought-tolerant and susceptible wheat genotypes in response to water stress. (July 2018) - Hu, Ling; Xie, Yan; Fan, Shoujin; Wang, Zongshuai; Wang, Fahong; Zhang, Bin; Li, Haosheng; Song, Jie; Kong, Lingan
Highlights: The root transcriptomes of two wheat genotype were examined under PEG treatment. DEGs related to antioxidative and antiosmotic stresses are more induced in JM-262. The feed-in to TCA cycle pathways may enable JM-262 to produce more biomass and energy. JM-262 could develop greater root systems to take up more water than LM-2. Hormone signaling may play key roles in root development and other responses to drought. Abstract: Water deficit is one of the major factors limiting crop productivity worldwide. Plant roots play a key role in uptaking water, perceiving and transducing of water deficit signals to shoot. Although the mechanisms of drought-tolerance have been reported recently, the transcriptional regulatory network of wheat root response to water stress has not been fully understood. In this study, drought-tolerant cultivar JM-262 and susceptible cultivar LM-2 are planted to characterize the root transcriptional changes and physiological responses to water deficit. A total of 8197 drought tolerance-associated differentially expressed genes (DEGs) are identified, these genes are mainly mapped to carbon metabolism, flavonoid biosynthesis, and phytohormone signal transduction. The number and expression level of DEGs involved in antioxidative and antiosmotic stresses are more enhanced in JM-262 under water stress. Furthermore, we find the DEGs related to root development are much more induced in JM-262 in phytohormone signal transduction and carbon metabolism pathway. In conclusion, JM-262 may alleviate the damage of drought by producing more osmoprotectants, ROS scavengers, biomass and energy. Interestingly, hormone signaling and cross-talk probably play an important role in promoting JM-262 greater root systems to take up more water, higher capabilities to induce more drought-related DEGs and higher resisitance to oxidative stresse.